If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -4 = 6x + -8 Reorder the terms: -4 + -3x = 6x + -8 Reorder the terms: -4 + -3x = -8 + 6x Solving -4 + -3x = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + -3x + -6x = -8 + 6x + -6x Combine like terms: -3x + -6x = -9x -4 + -9x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -9x = -8 + 0 -4 + -9x = -8 Add '4' to each side of the equation. -4 + 4 + -9x = -8 + 4 Combine like terms: -4 + 4 = 0 0 + -9x = -8 + 4 -9x = -8 + 4 Combine like terms: -8 + 4 = -4 -9x = -4 Divide each side by '-9'. x = 0.4444444444 Simplifying x = 0.4444444444
| (x^3y^2/x^4y^2)^2 | | 3x-2=5+5x | | a+y=b | | 4x-y+3z=0 | | 4a-(3a-2)=2(3a-2) | | e^2k=10 | | X+8+8-8x= | | -8x+21=3 | | (x-3)^(7/5)=128 | | 3/5÷2/3 | | 5(z+6)-2=9forz | | tan^-1(8/13) | | 5(y+1)=3 | | Abs(-7a)=28 | | sin(40)=8/x | | sin40=8/x | | F(x)=-4x^2+16 | | 6W+193=55 | | x+12=m+32 | | 8x-6x+25=35 | | 6(t-4)=3t+3 | | 8-6x+25=35 | | N^2+9n+9=0 | | 3(p+4)=2p-7 | | 5x+89=29 | | 2u+91=27 | | -7+0.25m=7 | | 0.8x+23=-25 | | 2x+24=18 | | 0.8x+23=25 | | -16a+67=3 | | 7x-35-3x=2x-13 |